Small-signal model of resonant link converter - Milanovič, Miro (Informacije MIDEM, 2003)
The conventional small signal modeling techniques as are state space averaging and injecting-absorbed current method are not appropriate for using in converters based on high frequency resonant link (HFRL). The mentioned methods are appropriate for processes where the switching frequency is constant. Because the operation frequency of the HFRL converters is load dependent the other way of modeling must be used. In this paper a small-signalmodel of the HFRL converter, operating with a variable resonant link frequency, is developed by using of the estimator for linear system (ELIS) which exists under MATLAB. The high frequency resonant link voltage is modulated by the low frequency signal. The Levenberg-Marguardt approximation method is used for evaluation of the magnitude and phase of the envelope of the high frequency resonant link voltage.
Keywords: elektronska vezja; modeliranje; napajanje; resonančni povezovalni krog; visokofrekvenčni resonančni pretvorniki